Lightweight freestanding hollow carbon fiber interlayer for high‐performance lithium‐sulfur batteries. (16th November 2021) - Meng, Qinglong; Yang, Rong; Liu, Ying; Li, Mingxu; Chen, Shaozheng; Yan, Yinglin
Summary: As a promising next‐generation energy storage device, lithium‐sulfur (Li‐S) batteries have the high theoretical energy densities, however, the notorious "Shuttling Effect" greatly impacts their commercialization. Herein, a freestanding hollow carbon fiber (HCF) derived from waste cotton tissues was designed as an interlayer for Li‐S batteries by one‐step carbonization at different temperatures. The inherently interwoven fibers and exceptional hollow structure of the carbon interlayers can effectively accelerate the reaction kinetics and restrain the "Shuttling Effect." Moreover, carbon interlayer can also act as an upper current collector to reutilize the active material, and further enhance the reversible capacities. In this study, the HCF‐800 carbon fiber interlayer was fabricated by carbonization at 800°C, which can endow the HCF interlayer with many profitable properties such as rich pore structures, excellent flexibility, and exceptional hollow tube structure. Therefore, the S/super‐P with HCF‐800 cell was shown the excellent cycling stability with 733 mAh g −1 at 0.1 C after 100 cycles. Even under a high sulfur loading of 2.23 mg cm −2, the cell also maintained a high capacity of 502 mAh g −1 after 100 cycles. Abstract : Hollow carbon fibers (HCFs) interlayer derived from waste cotton tissues. The unique hollow structure of HCFs effectively restrains the "Shuttling Effect." As an upper current collector, HCFs can not only reutilize the active material, but also enhance electrical conductivity.